The protective duration of Streptococcus agalactiae vaccine in Nile Tilapia for the prevention of streptococcosis - , Sukenda; , Rusli; Sri Nuryati; Dendi Hidayatullah (Jurnal Akuakultur Indonesia)
ABSTRACT